Changing trends in colorectal cancer in the Republic of Korea: contrast with Japan - Minjoo Yoon; Nicholas Kim; Byungho Nam; Jungnam Joo; Moran Ki (Epidemiology and Health, 2015)
Colorectal cancer has a high worldwide incidence. Japan, a country that is geographically and culturally similar to the Republic of Korea (here after Korea), has recently reported a decreasing trend in the incidence of colorectal cancer. However, Korea had the highest incidence of colorectal cancer among Asian countries in 2012. Our aim was to observe the changing trends in incidence and mortality of colorectal cancer in Korea and to compare them to those in Japan. Incidence data were collected from the Korean Central Cancer Registry and mortality data were collected from Korean Statistical Information Service. Incidence and mortality data on colorectal cancer in Japan were acquired from the National Cancer Center in Japan. Age-standardized incidence and mortality rates were determined based on Segi’s world population. Screening data from both countries were collected from the national cancer center in each country. In Korea, the age-standardized incidence rate of colorectal cancer in both sexes was 20.9 to 38.0 per 100,000 from 1999 to 2012 and the rate in males increased more dramatically than in females. In addition, the increase between 2002 and 2012 was first observed in the age group over 40. In Japan, the incidence of colorectal cancer has been more constant over recent years than in Korea. The age-standardized mortality rate of colorectal cancer in both sexes in Korea was 8.5 to 9.3 per 100,000 from 2000 to 2013, and the trend in mortality was constant during this period. In Japan, the mortality rate decreased slightly during the same period. Crude screening rates were increased overall in both Korea and Japan during the period studied. Since the incidence of colorectal cancer has increased in Korea, the control of this cancer is an important public health issue. As Japan has achieved a reduction in colorectal cancer, adjustment of Korea’s current systems for screening and treatment of colorectal cancer according to those of Japan may contribute to improved colorectal cancer control in Korea.